2019
DOI: 10.21467/anr.2.1.14-31
|View full text |Cite
|
Sign up to set email alerts
|

Green Peptide–nanomaterials; A Friendly Healing Touch for Skin Wound Regeneration

Abstract: The complex phenomenon by which the body responds to any injury of skin or tissue is known as wound healing. A number of phases like exudative, proliferative, and extracellular matrix remodeling are orchestrated events to be occurred involving blood cells, parenchymal cells, and different soluble mediators. Different internal, as well as external factors, regulate the speed and quality of healing. The delay in wound healing process causes the chronic wound or scar formation. At the present moment, the upscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 177 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…The main role of wound dressing includes maintaining wound hydration, absorbing excess wound secretions, minimizing the impact on the wound site, and as a barrier to the entry of foreign microorganisms into the wound site [ 17 , 18 , 19 ]. The nanofiber dressings as a product of nanotechnology were designed to decrease infection, irritation and improve wound healing by providing a positive environment in addition to their usual duties [ 20 , 21 ]. In comparison with macro-scale dressings, nanofibers contain more moisture in their structure and keep the wound area moist during the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…The main role of wound dressing includes maintaining wound hydration, absorbing excess wound secretions, minimizing the impact on the wound site, and as a barrier to the entry of foreign microorganisms into the wound site [ 17 , 18 , 19 ]. The nanofiber dressings as a product of nanotechnology were designed to decrease infection, irritation and improve wound healing by providing a positive environment in addition to their usual duties [ 20 , 21 ]. In comparison with macro-scale dressings, nanofibers contain more moisture in their structure and keep the wound area moist during the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…[37]. The wound healing properties of silver are reported in many in vivo studies where AgNPs promoted the healing process directly by reducing the cytokine-modulated inflammation [38]. The chance of infection can be decreased by covering the wounded area with these nanocoated bandages as reported by B. Pannerselvam et al in their study wherein they found increased wound recovery with increasing concentration of AgNPs [39].…”
Section: Immobilization Of Nanoparticles On Clothmentioning
confidence: 94%